Development of Learning Media Chemistry Puzzle Based on Islamic Integration of Science on Petroleum Materials - Ilma Amalia; Setia Rahmawan (South Sulawesi Education Development (SSED), 2024)
Integrating Islamic science and science can form positive student qualities, such as discipline and faith. However, there are still areas for improvement in teacher readiness and the creation of learning media that combine religion and science, especially chemistry lessons. This study aims to determine the feasibility of chemistry puzzle media based on the integration of Islamic science into petroleum materials. Development using the ADDIE model consists of analysis, design, development, implementation, and evaluation. The instruments in this study are validation sheets, product assessments, and student questionnaires. Products are validated by material and media experts, assessed by chemistry teachers, and in the responses of grade XI MIPA Madrasah Aliyah students. Qualitative data were tabulated and analyzed using the ideal assessment category to determine the quality of the media. The validation results by material and media experts on the media are considered very valid. The results of teacher assessment from the aspect of content and aspects of integration percentage of assessment 91.6%, percentage of 97.2% assessment of aspects of presentation and aspects of language and communication, 88.8% percentage of display aspects, 90.2% percentage of assessment aspects of typographic use and percentage of 95.8% assessment aspects of media organization. The results of the student response questionnaire get a very decent category. It was concluded that the media is considered very good and can be used as an innovation or alternative to learning integrated chemistry of petroleum materials. Based on an assessment of the overall ideal percentage of 92.6%.